POTENSI WISATA ALAM AIR TERJUN BONESOMPE DI DESA TINDAKI KECAMATAN PARIGI SELATAN KABUPATEN PARIGI MOUTONG - Maryani, Siti; Sudhartono, Arief (Universitas Tadulako, 2020)
In the South Morning area particularly in Tindaki Village there is the Bonesompe waterfall, with its waterfall height of approximately 15 meters and it has three levels. Access to this location is good enough although it must pass through a sizable river but can use what two-wheeler when the river water is not too heavy and passes through the community plantation heading to the waterfall site. So it is necessary for this study to know the potential value of Bonesompe waterfalls to be developed as a natural tourist destination area. The special purpose of the study is to find out the natural tourism potential of Bonesompe waterfall in Tindaki Village South Parigi Subdistrict of Parigi Moutong County. Research was carried out for two months, from April 2019 to May 2019, located in Tindaki Village South Parigi Subdistrict of Parigi Moutong County. The tools used in the study were Hp cameras. Whereas the materials used are interview guide sheets (attached), administrative region maps of research sites (attached), reports and past research theses and various support libraries as secondary data sources to help complement direct observations in the field. The method used in this study was qualitative descriptive. As for the results of the study obtained that potential feasibility analyzers result obtained value for each criterion was Attractiveness (86.11%), accessibility (79.16%), accommodation (50%), means and infrastructure (100%). Results showed that the Bonesompe waterfall was worth developing as one of the tourist destination areas with general feasibility presentage of 80.14%.Keywords: nature tourism potential, waterfalls